BİNA TASARIM PARAMETRELERİ DİKKATE ALINARAK PERDE KESME KUVVET TASARIMINA FARKLI BİR YAKLAŞIM - ŞAHİN, HÜMEYRA (Fırat Üniveristesi, 2015)
Betonarme perdeler depreme dayanıklı yapı tasarımında yaygın olarak kullanılan taşıyıcı sistem elemanlarıdır. Ancak betonarme perdelerin etkili olabilmesi deprem enerjisini sünek bir güç tükenmesi ile tüketmesine bağlıdır. Sünek bir güç tükenmesi için kesme kapasitesinin eğilme kapasitesinden yüksek olması gerekir. Yapılan çalışmalar kesme kuvvet talebinin, perde taban kesitinde elastik ötesi şekil değiştirmeler meydana geldikten sonra, eğilme kapasitesine ek olarak yüksek modların etkisi ile arttığını göstermiştir. Orta ve büyük şiddetli deprem yüklemeleri altında elastik ötesi şekil değiştirmelerin meydana geldiği perdelerde, kesme kuvvetinde momente oranla daha büyük artışlar meydana gelmektedir. Yüksek modların etkisini dikkate alan mod birleştirme yöntemi ile sadece birinci modun etkisini dikkate alan eşdeğer deprem yükü yöntemi, elastik ötesi davranışı dikkate almadığı için kesme kuvvet tahmininde yetersiz kalmaktadır. Perde kesme kuvvetinde meydana gelen artışın, gevrek kırılmalara neden olacağı birçok çalışma ile gösterilmiştir. Elastik ötesi durumda perdelerde meydana gelen kesme kuvvet artışı, dinamik büyütme kat sayısı (?v) ile Türk Deprem Yönetmeliği'nde (2007) dikkate alınmıştır. Bu tez çalışmasında, Türk Deprem Yönetmeliği'nde sabit kat sayılar 1.0 ve 1.5 ile ifade edilen dinamik büyütme katsayısı (?v), periyod (T), davranış katsayısı (R) ve perde boy/en oranı (Hw/Lw) değişkenleri dikkate alınarak sayısal olarak incelenmiştir. Elastik ötesi analizler neticesinde ?v'yi sabit tek bir sayı ile tanımlamanın yetersiz olduğu görülmüştür. Çalışmada ?v için, biri grafik tabanlı diğeri de formüle dayanan iki yaklaşım sunulmuştur. Ayrıca Türk Deprem Yönetmeliği tarafından önerilen kesme kuvvet dağılımın yetersiz olduğu görülmüş ve kesme kuvvet dağılımı için bir eğri önerilmiştir.

Reinforced shear walls, which are structural elements, are widely used in earthquake resistance structural design. Effectiveness of reinforced shear walls significantly depends on the energy consumed in its inelastic behavior. For a ductile the behavior shear force capacity should be higher than moment capacity. Shear and moment demand is large at a ductile behavior. When in the design of the shear walls, the equivalent static seismic load is used, only the first mode is considered and the effects of the higher modes are not taken into account. However, this efficiency can be avoided, when the modal superposition method is employed. All the method reflects the elastic behavior shear wall. Since inelastic deformation is allowed in the moderate and higher seismic events, the shear and bending moment variation along the shear wall should be modified. When a plastic hinge develops at the base section of the shear wall, then inelastic ductile deformations occurs. However, the shear force variation displays an increase more than the moment due to inelastic behavior. Consequently a brittle failure will be unavoidable, when design is carried out by taking elastic analysis results, even if higher modes are considered, because the shear demand is large than moment demand in the inelastic behavior. The higher mode effect and inelastic behavior has been considered in the Turkish Seismic Design Code (2007) using dynamic shear amplification factor (?v) which is given 1.0 and 1.5 depending on the contribution of the shear walls in resisting seismic shear wall. In this thesis, dynamic shear amplification factor (?v) is investigated numerically with parameters like as first mode period (T), strength reduction factor (R) and shear wall length/width ratio (Hw/Lw) by considering higher modes and inelastic deformation. The analysis yields that this parameters is not constant, as expected, depends on various properties of system. The results for the dynamic shear amplification are presented graphical as well as a relationship. Additionally, a story shear force profile curve, which more realistic than the given the Turkish Seismic Design Code (2007) has been proposed.
An unusual approach to determine shear force while shear wall design by using different design parameters
Keywords: İnşaat Mühendisliği